The effects of elevated CO2 and water stress on C2 pasture species (Blepharis linariifolia and Cenchrus biflorus) native to Sudan - Zaki-Eldeen, Sumaya (Trinity College (Dublin, Ireland). Department of Botany, 2001)
A doubling of the pre-industrial atmospheric CO2 concentration (~280 ppmv) is expected by the middle of this century, if the current rate of growth in the annual emission of fossil carbon is maintained. The effects of elevated CO2 concentrations on native Sudanese plant species has received very little attention to date. In tliis study a number o f experiments investigated the effects of elevated CO2, under both optimimi and waterstressed condition, on two pasture species native to the western part of Sudan; these were Blepharis linariifolia (dicot) and Cenchrus hiflorus (monocot). The study of photosynthetic characteristics (anatomy and physiology) confirmed that both B. linariifolia and C. biflorus are C4 species. The anatomical studies suggested that C. biflorus is an NADP-ME subtype while B. linariifolia is an NAD-ME subtype.
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin